Study of ramped temperature influence on MHD convective chemically reactive and absorbing fluid past an exponentially accelerated vertical porous plate (Journal of Naval Architecture and Marine Engineering, 2018)
A systematic study has been performed on MHD convective chemically reactive and absorbing fluid along an exponentially accelerated vertical plate with the impact of Hall current by considering ramped temperature. Laplace transform technique is applied to obtain exact solutions of the non-dimensional governing equations for fluid velocity, temperature and concentration. Based on these solutions, the expressions for skin friction coefficient, Nusselt number and Sherwood number are also derived. The consequences of diverse physical parameters on flow quantities are examined thoroughly with graphical representations. The numerical values for skin friction coefficient, rate of heat transfer and rate of mass transfer are recorded and analyzed.